Joint external evaluation of the International Health Regulation (2005) capacities: current status and lessons learnt in the WHO African region. Issue 6 (1st November 2019) - Talisuna, Ambrose; Yahaya, Ali Ahmed; Rajatonirina, Soatiana Cathycia; Stephen, Mary; Oke, Antonio; Mpairwe, Allan; Diallo, Amadou Bailo; Musa, Emmanuel Onuche; Yota, Daniel; Banza, Freddy Mutoka; Wango, Roland Kimbi; Roberts, Nathalie Amy; et al.
Abstract : The International Health Regulations (IHR, 2005) are an essential vehicle for addressing global health security. Here, we report the IHR capacities in the WHO African from independent joint external evaluation (JEE). The JEE is a voluntary component of the IHR monitoring and evaluation framework. It evaluates IHR capacities in 19 technical areas in four broad themes: 'Prevent' (7 technical areas, 15 indicators); 'Detect' (4 technical areas, 13 indicators); 'Respond' (5 technical areas, 14 indicators), points of entry (PoE) and other IHR hazards (chemical and radiation) (3 technical areas, 6 indicators). The IHR capacity scores are graded from level 1 (no capacity) to level 5 (sustainable capacity). From February 2016 to March 2019, 40 of 47 WHO African region countries (81% coverage) evaluated their IHR capacities using the JEE tool. No country had the required IHR capacities. Under the theme 'Prevent', no country scored level 5 for 12 of 15 indicators. Over 80% of them scored level 1 or 2 for most indicators. For 'Detect', none scored level 5 for 12 of 13 indicators. However, many scored level 3 or 4 for several indicators. For 'Respond', none scored level 5 for 13 of 14 indicators, and less than 10% had a national multihazard public health emergency preparedness and response plan. For PoE and other IHR hazards, most countries scored level 1 or 2 and none scored level 5. Countries in the WHO African region are commended for embracing the JEE to assess their IHR capacities. However, major gaps have been identified. Urgent collective action is needed now to protect the WHO African region from health security threats.